2018
DOI: 10.5194/essd-2017-109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GRACILE: A comprehensive climatology of atmospheric gravity wave parameters based on satellite limb soundings

Abstract: Abstract. Gravity waves are one of the main drivers of atmospheric dynamics. The spatial resolution of most global atmospheric models, however, is too coarse to properly resolve the small scales of gravity waves, which range from tens to a few thousand kilometers horizontally, and from below 1 km to tens of kilometers vertically. Gravity wave source processes involve even smaller scales. Therefore, general circulation models (GCMs) and chemistry climate models (CCMs) usually parametrize the effect of gravity w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(116 citation statements)
references
References 20 publications
(33 reference statements)
9
106
1
Order By: Relevance
“…Additionally, these calculations are an average estimate over the entire flight path, and localized MFs due to stronger phases over the mountains and directly in the lee of the mountains likely have larger associated MFs. Regardless of this, the spectral MF calculations show MF values that are larger than the average background MF values previously measured by radars and satellites, which have ranged from ~1 to 20 m 2 /s 2 (Ern et al, ; Fritts et al, , ; Fritts & Vincent, ; Murphy & Vincent, ; Nakamura et al, ; Reid et al, ; Tsuda et al, ; Vincent & Reid, ; Wang & Fritts, ). This finding is qualitatively in good agreement with Hertzog et al (), who showed that MW events are particularly intermittent and strong events can carry very large MFs.…”
Section: Temperature and Mf Measurements And Validationmentioning
confidence: 73%
“…Additionally, these calculations are an average estimate over the entire flight path, and localized MFs due to stronger phases over the mountains and directly in the lee of the mountains likely have larger associated MFs. Regardless of this, the spectral MF calculations show MF values that are larger than the average background MF values previously measured by radars and satellites, which have ranged from ~1 to 20 m 2 /s 2 (Ern et al, ; Fritts et al, , ; Fritts & Vincent, ; Murphy & Vincent, ; Nakamura et al, ; Reid et al, ; Tsuda et al, ; Vincent & Reid, ; Wang & Fritts, ). This finding is qualitatively in good agreement with Hertzog et al (), who showed that MW events are particularly intermittent and strong events can carry very large MFs.…”
Section: Temperature and Mf Measurements And Validationmentioning
confidence: 73%
“…; Ern et al . ) suggest that, for the same season, altitude and geographic regions as the peaks in TC‐associated GW activity, typical mean levels of momentum flux are ∼0.5 mPa over the whole of each region, compared to basin‐ total estimates of the same order for TCs. While some fraction of the GWs included in these reference averages will be from TCs, and even allowing for the possibility that the bulk of the time‐mean TC‐associated momentum flux is concentrated in short bursts with much higher local values, the additional momentum flux suggested by my results to be attributable to TCs specifically is small, and is thus very unlikely to be a major factor in the overall circulation.…”
Section: Contribution To the Global Gw Momentum Flux Budgetmentioning
confidence: 99%
“…The maximum value of 130% occurs during June and September but not during July and August. This might be related to the fact that the GW generation over the oceans from spontaneous emission is strongest during July and August (Figures 13 and 14 of Ern et al, ). This imposes a stronger zonal‐mean component of the GW activity during July–August.…”
Section: Global Distributions Of the Primary And Larger‐scale Secondamentioning
confidence: 99%